The Impact of Halal Food Scm Integration on Quality Performance (Case Study on Msme in Bandung City) - Wira Pramana Putra; Ratih Hendayani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to find out how big and the impact of internal integration, supplier integration, customer integration which has a halal integrity dimension in it, namely halal raw material integrity, halal production integrity, and information integrity on quality performance in halal food SMEs in Bandung City. This research uses quantitative methods. The data was obtained through a survey method through an online questionnaire addressed to 100 halal food MSME owners in the Bandung City. The data analysis technique used is SEM-PLS using SmartPLS with measurement model and hypothesis testing using bootstrapping technique. Based on the data analysis technique carried out using SmartPLS, the findings in this study show that internal integration has a positive and significant effect on supplier integration and customer integration. Internal integration has no positive and insignificant effect on halal raw material integrity, but has a positive and significant effect on halal production integrity and information integrity. Supplier integration has a positive and significant effect on halal raw material integrity, but has no positive and insignificant effect on halal production integrity. Customer integration does not have a positive and insignificant effect on halal production integrity, but has a positive and significant effect on information integrity. Halal raw material integrity has no positive and significant effect on quality performance, but halal production integrity and information integrity have positive and significant effect on quality performance. This research provides new insights to the owners of halal food SMEs in Bandung City and provides advice to halal food SMEs in Bandung City based on the value of the greatest impact, to maintain and improve the implementation of information integrity in order to maintain the continuity and consistency of quality performance of halal food SMEs in the Bandung City.